Environmental awareness among faculty members at the University of Derna Study summary (Journal of Libya for geographical studies, 2023)
The study aimed to reveal the level of environmental awareness among faculty members at the University of Derna . The results showed that the level of environmental awareness of the study sample according to its three main axes, which are the axis of rationalizing paper consumption and sustainable development and the axis of saving energy consumption and sustainable development, and the axis of waste and recycling and sustainable development, Where the percentage of awareness for all of the above axes was as follows (66.7%, 85% and 74.15) respectively for the three axes. But if we extract the average of the three axes together, we get an awareness level of (75.2%), and thus we can say that the level of awareness in general Fairly acceptable to faculty members.
Keywords: Level Of Environmental awareness; Sustainable; Teaching Staff; University Of Derna